Embedding isochronous cells overland flow module into MODFLOW. Issue 26 (5th September 2012) - Zhang, Bo; Hong, Mei; Zou, Zuhao; Yeh, Tian‐Chyi Jim; Cheng, Pin
Abstract This study integrates a simple overland flow module (isochronous cells model) with the river module of MODFLOW such that temporal and spatial interactions between stream flow and groundwater can be simulated using net rainfall data of a watershed. The isochronous cells model is an efficient travel time runoff approach based on geographic information system (GIS) that considers both spatial and temporal variations of net rainfall through hill slope of the watershed. This overland module is easily coupled with MODFLOW river routing module. Specifically, the stream flow from the isochronous cells model is directly assigned to both sides of river cells of the MODFLOW model. Such an integration of MODFLOW and isochronous cells model is especially useful in watersheds where river flow data are limited. The feasibility of this integrated model was demonstrated using a case study in the middle and downstream regions of the Yitong River watershed, China. Copyright © 2012 John Wiley & Sons, Ltd.